Bahasa Melayu for International Students (BMfIS) 2012 - Siti Muslihah, Isnain; Ezihaslinda, Ngah (Pusat Bahasa Moden dan Sains Kemanusiaan, 2012)
Bahasa Melayu for International Students (BMfIS) was held for the second time at the Centre for Modern Languages and Human Sciences, Universiti Malaysia Pahang. The second group involved two students from the University of Illinois Northern (NiU), Matthew Ropp and Derek Koegel aged 21 and 22 years old. The program aimed to expose the American students to an authentic learning environment in getting to know more about Malay customs and culture. The driving force behind the program who also acted as the module developers were Professor James T. Collins, Director of Asian Studies, NiU, Dr Nik Aloesnita Mohd Alwi, Dr Zailin Shah Yusoff and Siti Muslihah Isnain. The program was also supported by five facilitators cum tutors for in-class learning. They were Nurainatul Fatimah Burhanuddin, Lai Yew Chong, Rozanne Shamini d/o Francis, Muhammad Adib Mat Nasir and Chok Choy Hong.